Некоторые вопросы ограничения права собственности при расследовании преступлений - Митюкова, Марина (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at an analysis of the relationship between civil law and the criminal procedure law system. The author focus on the limitation of the property right in the selected aspects of the criminal proceedings.